Supporting Factors For The Success Of Micro-Scale Cattle Farming Businesses (MSMEs) - Novandriansyah, Andiko; Wijaya Negara, Adhona Bhajana (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The success of micro-scale cattle farming businesses (MSMEs) plays a crucial role in strengthening the agricultural sector and supporting rural economic development. This study aims to identify and analyze the key factors that contribute to the success of MSMEs in the cattle farming industry. Utilizing both qualitative and quantitative approaches, the research examines internal and external elements that influence business performance. Internal factors include the farmer's managerial skills, financial management, livestock health management, and access to quality feed. External factors encompass government policies, market accessibility, infrastructure availability, and the role of community networks and cooperatives. Findings indicate that the synergy between these factors significantly enhances productivity, sustainability, and profitability. The study concludes that targeted interventions, capacity-building programs, and policy support are essential to empower cattle farming MSMEs and ensure their long-term success. These insights provide valuable guidance for stakeholders, including policymakers, researchers, and practitioners, to foster a robust and sustainable cattle farming sector